2023
DOI: 10.54393/tt.v4i1.118
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Burnout Syndrome with Musculoskeletal Disordersand Its Prevalence Among Medical Students

Abstract: Burnout is common exhaustion in students especially among medical students due to their increased study hours, increased demands according to the education sector and less tolerance. Objective: To determine the prevalence and correlation of burnout syndrome and musculoskeletal problems among university students in Lahore. Methods: The analytical cross-sectional study was conducted by including 181 medical students by using, a convenience sampling technique according to the predefined selection criteria. The Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The sample size was calculated by taking the reference from Tanveer et al. (2023), who reported trouble in the knee during the last 12 months in 8.3% of participants. By using the open epi sample size calculator, a sample size of 117 was calculated and hence we recruited 133 participants through the purposive sampling technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated by taking the reference from Tanveer et al. (2023), who reported trouble in the knee during the last 12 months in 8.3% of participants. By using the open epi sample size calculator, a sample size of 117 was calculated and hence we recruited 133 participants through the purposive sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…Burnout in physiotherapy may be caused by a heavy workload or a lack of management support(Álvarez-Hernández et al, 2010;O'Shaughnessy & Tilki, 2007). Many MSDs, especially muscular pain in the neck, shoulder, upper, and lower back, are caused by BS(Tanveer et al, 2023). Aljadani et al also reported that 65% of medical students suffer from MSD, particularly those with burnout…”
mentioning
confidence: 99%